The Use of Gadget in Instilling Religious and Moral Values to Early 5-6 Aged Childhood - Hidayat, Yusuf; Rahmawati, Risa; Ihsanda, Nu'man; Sugiarti, Sri; Tya, Sandi (Universitas Muhammadiyah Ponorogo, 2025)
The development of religious and moral values is the ability of early childhood to act and behave according to the religious and moral values they embraced. This study aims to find out the effect of using gadget on instilling religious and moral values for early childhood in Kober El Karim, and to find out the benefits of using gadget for early childhood in Kober El Karim. The method used in this study is a qualitative under a phenomenological approach. The results of the present study show that the early childhoods’ religious and moral values are seen in the form of reading basmalah in beginning every activity, saying a prayer before and after learning, before and after eating snacks, and before going home. Besides, the early childhoods also speak the truth and maintain their noble deeds while they are at school and at home. In addition, the benefits of using gadget to early childhood will be: gadget is able to generate the early childhood’s self-confidence, gadget is able to foster the early childhood’s creativity according to what he/she watched, gadget is able to develop early childhood’s fine and gross motor skills, gadget is able to increase the early childhood’s linguistic skill through increasing his/her vocabularies based on the materials he/she watched.